The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.14814/phy2.12821
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose oral cadmium increases airway reactivity and lung neuronal gene expression in mice

Abstract: Inhalation of cadmium (Cd) is associated with lung diseases, but less is known concerning pulmonary effects of Cd found in the diet. Cd has a decades‐long half‐life in humans and significant bioaccumulation occurs with chronic dietary intake. We exposed mice to low‐dose CdCl2 (10 mg/L in drinking water) for 20 weeks, which increased lung Cd to a level similar to that of nonoccupationally exposed adult humans. Cd‐treated mice had increased airway hyperresponsiveness to methacholine challenge, and gene expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 65 publications
(80 reference statements)
1
25
0
Order By: Relevance
“…For these studies, the mouse food was nominally Cd-free, equivalent to intake of 0.04 mg/L in the drinking water (Chandler et al 2016). Lung samples were harvested from the mice at the end of 16 weeks and the left lobes of lung tissues treated with 10% neutral formalin for fixation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For these studies, the mouse food was nominally Cd-free, equivalent to intake of 0.04 mg/L in the drinking water (Chandler et al 2016). Lung samples were harvested from the mice at the end of 16 weeks and the left lobes of lung tissues treated with 10% neutral formalin for fixation.…”
Section: Methodsmentioning
confidence: 99%
“…We use 1 μM as our in vitro reference dose (Go et al 2013a, b) because this is similar to the concentration found in human lung (Chandler et al 2016), does not cause cell death, and activates proinflammatory signaling similarly to that observed with mouse models in which oral Cd is provided to raise lung Cd to values similar to human lung Cd content (Chandler et al 2016). Our previous study of Cd in this range showed that Cd disrupts actin cytoskeleton regulation in lung fibroblast by stimulating actin polymerization (Go et al 2013a).…”
Section: Introductionmentioning
confidence: 99%
“…Male C57BL6 mice (n = 11 -13 per group) aged 8 weeks (Jackson Labs, Bar Harbor, ME, USA) were maintained in clean facilities and given sterile-filtered drinking water with 1 mg/L CdCl 2 (Sigma-Aldrich, St. Louis, MO, USA) or vehicle for 16 weeks. Food content of Cd (62 ± 1 ng/g food) was negligible compared to the Cd derived from water (1). Ten days prior to study completion, mice were inoculated with H1N1 (A/California/04/2009; dose of 0.6 x 10 3 pfu) under isoflurane anesthesia.…”
Section: Animalsmentioning
confidence: 99%
“…Lung tissue 114 Cd was assayed as previously described (1). ICP-MS procedures conformed to accuracy (100 ± 10%) and precision standards (relative standard deviation < 12%).…”
Section: Measurement By Inductively-coupled Plasma Mass Spectrometmentioning
confidence: 99%
See 1 more Smart Citation